Perspectives of Registered Nurses in Involving the Family Members of MHCUs Admitted in Specialized Mental Health Establishments in Limpopo Province, South Africa - Shimange, Mihloti E; Shilubane, Hilda N; Lowane, Mygirl P (International Journal of Innovative Research and Scientific Studies, 2025)
The study aimed to describe registered nurses' perspectives on involving the family members of mental healthcare users (MHCUs) admitted to specialized mental health establishments in Limpopo Province, South Africa. An explanatory and descriptive quantitative approach was employed to determine registered nurses’ perspectives on involving family members in the care of MHCUs. A self-developed questionnaire was used to gather data from 150 respondents who consented to participate in the study. A Statistical Package for the Social Sciences version 29 of 2022 was used and data were presented in frequency tables, graphs, and pie charts. A multi-factor dimension was captured as the viewpoints of registered nurses on collaborating with family members during the care of the MHCUs. The study revealed that registered nurses in mental health establishments have no challenge involving family members in the treatment of MHCUs. However, it was also reported that it is not always easy to contact family members as most stay in areas with poor signals. The researchers observed a need for policy revisions to encourage family involvement and increased resources for mental health care establishments.